2000
DOI: 10.1007/s002390010099
|View full text |Cite
|
Sign up to set email alerts
|

Addition of wsp Sequences to the Wolbachia Phylogenetic Tree and Stability of the Classification

Abstract: Wolbachia are symbiotic bacteria altering reproductive characters of numerous arthropods. Their most recent phylogeny and classification are based on sequences of the wsp gene. We sequenced wsp gene from six Wolbachia strains infecting six Trichogramma species that live as egg parasitoids on many insects. This allows us to test the effect of the addition of sequences on the Wolbachia phylogeny and to check the classification of Wolbachia infecting Trichogramma. The six Wolbachia studied are classified in the B… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
17
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 1 publication
2
17
0
Order By: Relevance
“…Two T. pretiosum lines (Tpret-06 and Tpret-13) fell within the group of T. deion (Dei) and the three others lines fell within the merged group Sib (Sib + Kay) proposed by Pintureau et al (2000). In addition, that proposal is in agreement with this study and was confirmed by including many other sequences from the GenBank database (Figure 1).…”
Section: Resultssupporting
confidence: 87%
See 3 more Smart Citations
“…Two T. pretiosum lines (Tpret-06 and Tpret-13) fell within the group of T. deion (Dei) and the three others lines fell within the merged group Sib (Sib + Kay) proposed by Pintureau et al (2000). In addition, that proposal is in agreement with this study and was confirmed by including many other sequences from the GenBank database (Figure 1).…”
Section: Resultssupporting
confidence: 87%
“…The Wolbachia strains that infect T. cordubensis and T. brevicapillum also belong to Sib group. Inclusion of the Wolbachia from T. cordubensis in Sib group agrees with the results obtained by Pintureau et al (2000). T. brevicapillum was also classified in the same group as T. cordubensis and its classification in the B group was shown by von der Schulenburg et al (2000) using the ftsZ gene.…”
Section: Resultssupporting
confidence: 84%
See 2 more Smart Citations
“…PCR amplification was carried out according to the protocol of Pintureau et al (2000). After amplification, 10 ll of the reaction mixture was electrophoresed with a 100 bp DNA ladder size standard (GibcoBRL) on 1.5% agarose minigels.…”
Section: General Pcr Amplificationmentioning
confidence: 99%